Selected problems of medical tourism – development, benefits, customers. Case of Poland - Haberla, Marcin; Kuźmińska-Haberla, Aleksandra (Economics of the 21st Century, 2015)
Poland has quickly become an important center for the medical tourism. It could be argued that soon it will be the leader in Central Europe – now ranks just behind Hungary and the Czech Republic. Poland seems to be attractive for patients not only from neighboring countries like Germany or Russia, but also from Scandinavia or the USA. Foreign customers appreciate innovative offer, high quality services on affordable prices, excellent skills of medical stuff, good location with rich natural environment. The aim of the article is to present the main characteristics of Polish medical tourism market and its customers. The article presents the major determinants of development of Polish medical tourism, the most important benefits offered by the rapid growth of this field of economy and concerns about medical tourists. Furthermore the article shows general classifications of medical tourists and also characteristics of main groups of this kind of tourists in Poland. The research employs secondary data collected from the relevant literature concerning medical tourism, kinds of medical tourists and data on medical services for foreigners in Poland
Ekonomia XXI Wieku = Economics of the 21st Century, 2015, Nr 4 (8), s. 99-111
Keywords: medical tourism; medical tourists; foreign tourism; turystyka medyczna; turysta medyczny; turystyka międzynarodowa